"Unsere Bürgerschaft befindet sich im Himmel" (Phil 3, 20): ein biblisches Motiv und seine Entwicklung im frühen Christentum - Schinkel, Dirk (Biblische Notizen, 2007)
”Our citizenship is in heaven” (Philippians 3:20) – this is the starting point for the interpretation of the biblical motif from Paul to the Epistle to Diognetos (5:9). “Social integration and separation” is an important factor in early Christian communities and literature from Paul to Clement from Alexandria. This article also illuminates the philosophical (stoic and cosmological) influences on this motif in the times of Marc Aurel and Lucian.